2015
DOI: 10.7448/ias.18.6.20302
|View full text |Cite
|
Sign up to set email alerts
|

Addressing gender inequalities to improve the sexual and reproductive health and wellbeing of women living with HIV

Abstract: IntroductionGlobally, women constitute 50% of all persons living with HIV. Gender inequalities are a key driver of women's vulnerabilities to HIV. This paper looks at how these structural factors shape specific behaviours and outcomes related to the sexual and reproductive health of women living with HIV.DiscussionThere are several pathways by which gender inequalities shape the sexual and reproductive health and wellbeing of women living with HIV. First, gender norms that privilege men's control over women an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
57
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 68 publications
(46 reference statements)
4
57
0
3
Order By: Relevance
“…The participants in this study were 55 HIV-positive women referring to the Shohada Comprehensive Health Center in Hamadan. The high mean of the stigma (119.98) before the intervention indicates that stigma is one of the most important health problems in HIV-positive women.Our findings are consistent with previous studies[ Amin et al (2015) asserted that stigma, discrimination, poor social support, violence, and mental health problems (e.g., depression and neurological disorders) are big challenges for people with HIV, especially for women[ 28] Baugher et al (2017). reported that nearly 8 out of every 10 people with HIV experienced stigma.…”
supporting
confidence: 93%
“…The participants in this study were 55 HIV-positive women referring to the Shohada Comprehensive Health Center in Hamadan. The high mean of the stigma (119.98) before the intervention indicates that stigma is one of the most important health problems in HIV-positive women.Our findings are consistent with previous studies[ Amin et al (2015) asserted that stigma, discrimination, poor social support, violence, and mental health problems (e.g., depression and neurological disorders) are big challenges for people with HIV, especially for women[ 28] Baugher et al (2017). reported that nearly 8 out of every 10 people with HIV experienced stigma.…”
supporting
confidence: 93%
“…This context includes gender inequality as a determinant on its own and in combination with other social and economic inequalities including: unequal power dynamics in interpersonal relationships, harmful gender and other socio-cultural norms and practices, limited economic circumstances, lack of access to education, limited employment opportunities, poor living conditions, disability, ethnicity, as well as the challenging political and legal environments where they live[1]. Studies have shown that harmful gender norms that promote male dominance over women prevent women from practicing safer sex, limit their use of contraceptives, and increase their risk of STIs, including HIV[2]. Similarly, research has also shown a relationship between violation and neglect of human rights and negative health outcomes and emphasizes the need to better integrate human rights approaches into interventions, particularly with attention to provider training, service delivery, raising awareness and capacity building[3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…These women are more prone to engage in unwanted sexual activities, and they also have little likelihood of experiencing safe sex. In addition, the stigma associated with HIV and consequent employment issues cause financial insecurity and related consequences (Amin, 2015;Robinson et al, 2017). In our setting, we found significant differences between assertive and non-assertive groups in terms of pregnancy experience, having live children, and number of children.…”
Section: Discussionmentioning
confidence: 62%